The Mechanical Properties of Portland Cement Reinforced by Short and Long Particles Made from Different Metals - Taha Abdullah (Journal of Pure & Applied Sciences, 2018)
This work investigates the effects of adding different types of metals (aluminum, galvanized steel and copper) of short (2 mm length) and long (5 mm length) particles to the cement matrix phase. The aim was to increase the compressive mechanical properties of the concrete by strengthening it with different types and lengths of certain metals. The new metal particles can be successfully combined into the cement paste. It was found that the short and long particles of aluminium have negative effects on the compressive mechanical properties. The failure stress of these reinforced materials decreased as compared to the unreinforced cement. However, there were some increases in failure stress in the steel-cement composite specimens due to the reinforcement using steel short and long-particles. The average failure stresses reached 15 and 19 MPa (for the short 2 mm and long 5 mm particles reinforced cements respectively), as compared to that of unreinforced cement. Moreover, there were noticeably large increase in failure stress in the metal-cement composite specimens was achieved due to the reinforcement of short and long-particles of cupper. The average failure stresses were increased to 12.6 and 26.6 MPa (for the short 2 mm and long 5 mm particles reinforced cements respectively). These values are higher than that of unreinforced cement with an average failure stress of 10.6 MPa. Finally, it was concluded that the addition of different types and length of metal can increase the specific strength (?/?) of cement, with the highest increase obtained by the reinforcement condition where long (5 mm) cupper particles are used. The average value reached 8.2 MPa g-1 cm-3 as compared to an average value of 5 MPa g-1 cm-3 for the unreinforced cement specimens.